New names for a few Indian flowering plants - Kumar, Venkatachalam Sampath; Karthikeyan, Saravanam (Phytotaxa, 2020)
While preparing the checklist of Indian flowering plants, it was noticed that some of the plant names currently accepted are indeed later homonyms. New names are proposed here for such later homonyms. Apart, while transferring the species from Gymnema Robert Brown (1810: 461) to Marsdenia Robert Brown (1810: 460) and from Pauia Deb & Ratna Dutta (1965: 363) to Atropa Linnaeus (1753: 181), the specific epithets are pre-empted in the respective genus and hence new names are proposed here.